Three new species of Remaneicaris Jakobi, 1972 (Copepoda, Harpacticoida, Parastenocarididae) from the Ribeirão do Ouro River, Minas Gerais, Brazil, with some remarks on the groundpattern of the Parastenocarididae - Corgosinho, Paulo Henrique C.; Arbizu, Pedro Martínez; Santos-Silva, Edinaldo Nelson Dos (Zootaxa, 2007)
Three new species of the parastenocaridid genus Remaneicaris Jakobi, 1972 were discovered in interstitial near-shore waters of the small river Ribeião do Ouro (a tributary of the Paraopeba river, in the São Francisco hydrographic basin). Remaneicaris tridactyla n. sp., R. paratridactyla n. sp. and R. juliae n. sp. are described in detail. The presence of a 1- segmented endopod on the male leg 3, previously reported for some Remaneicaris species, is confirmed here, and the phylogenetic relevance of this structure is discussed. These new species differ from each other by the shape of the leg 3 exopod and endopod, shape of leg 4 endopod, ornamentation of the telson and previous urosomites, and by the number of sensilla and dorsal pores. Some remarks on the groundpattern of the Parastenocarididae are given.